Pola Asuh Orang Tua Dalam Membentuk Kepribadian Anak Usia Dini - Budiman; Husaen Sudrajat; Alawiyah, Tuti (STAI Al-Amin Gersik Kediri Lombok Barat NTB, 2025)
Parenting is a process of in ifluencinng a person, where parents instill values they believe in to theirs children in the form of interaction that include leadership, nurturing, educating, guiding and protecting children from the time they are in the wobm until they grow up to become people who are useful for the religion, nation and state. Parent have various specific obligations, these obligations include fulfilling, guiding, educating, and also raising their children with appropripate and correct foundation based on the teachings of the religion they ad here to, by providing teaching and learning to their children. The aim of this research is ti find out how parents parenting patterns shape the personality of early childood at PAUD Al-Hikmah Bebuak. The type of research used is qualitative research. In the data collection process, researchers used several methods, namely interview, observation and documentation methods. Meanwhile for data analysis, researchers used qualitative descriptive analysis techniques, namely inthe form of written and verbal presentation of data from research objects at the institution. Based on the research result, it can be concluded and understood that parenting patterns in shapping the personality of early childhood in PAUD Al-Hikmah Bebuak Kopang District Central Lombok Regency have been carried out well. This is proven that children have begun to be able to speak politely and behave well towards everyone, have a religious attitude, are not selfish, respect other people, and aredisciplined in everyday life.